Simultaneous determination of tantalum, niobium, thorium and uranium in placer columbite-tantalite deposits from the Akim Oda District of Ghana by epithermal instrumental neutron activation analysis - Dampare, S.B.; Nyarko, B.J.B.; Osae, S.; Akaho, E.H.K.; Asiedu, D.K.; Serfor-Armah, Y.; Nude, P. (Journal of Radioanalytical and Nuclear Chemistry, 2005)
Tantalum, niobium, thorium and uranium contents of 21 columbite-tantalite minerals from the Akim Oda District of Ghana have been determined using epithermal instrumental neutron activation analysis (ENAA) with a conventional counting system. As thermal neutron filters, boron carbide was encapsulated in the irradiation vials during irradiation. The samples were irradiated at one of the outer irradiation channels in the Ghana Research Reactor-1 facility, and counted directly. Various elements were identified and quantified using 172 keV of 182mTa, 871 keV of 94mNb, 86.5 keV of 233Th and 74.7 keV of 239U. The precision and accuracy of the method were evaluated using standard reference materials and the precision was found to be within 5% with comparable accuracy. The composition of columbite-tantalite minerals ranged from 33.1% to 59.2% Ta2O5 and 19.2% to 44.6% Nb2O5, ThO2 and U3O 8 the levels were 0.024-0.045% and 0.014-0.048%, respectively. © 2005 Akadémiai Kiadó.
Keywords: Uranium; Niobium; Tantalum; Thorium; Instrumental Neutron Activation Analysis